GROWTH FACTORS IN GUIDED TISSUE REGENERATION - Samuel, Renata O. [UNESP]; Gomes Filho, João Eduardo [UNESP]; Araújo, Gustavo Sivieri de [UNESP]; Jacinto, Rogério de Castilho [UNESP]; Dezan Junior, Eloi [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (My University, 2020)
Advances in tissue engineering have provided excellent results in regeneration. These concepts have been increasingly used successfully in Odontology. Guided tissue regeneration (GTR) involves the use of a membrane to contain the clot at the treatment site and promote regeneration. The objective of current research is to improve the technique by combining biomaterials and bioactive molecules, as well as improving the tissue engineering techniques. Bioactive molecules such as growth factors are capable of inducing morphogenic signals, promoting angiogenesis, differentiation, and cell proliferation. Growth factors are at the center of many studies, but there is no consensus about the advantage of using bioactive molecules or the growth factors to be used in specific clinical scenarios. Bone morphogenic proteins (BMPs), platelet-derived growth factor (PDGF), and peptides of the parathyroid hormone (PTH) have been studied. BMPs have been associated with bone regeneration. However, this characteristic is more evident when BMPs are mixed with a biomaterial that supports the clot. PDGF has been shown to be mitogenic and chemotactic for periodontal ligament cells, with the additional effect of promoting regeneration of bone, ligament, and cement. PTH has been shown to exert multiple anabolic effects on both cancellous and cortical bone. This review makes a comparative evaluation of results from clinical and histological studies using growth factors in animal models and humans.
Keywords: growth factors; guided tissue regeneration